Irradiation Haematopoiesis Recovery Orchestrated by IL-12/IL-12Rβ1/TYK2/STAT3-Initiated Osteogenic Differentiation of Mouse Bone Marrow-Derived Mesenchymal Stem Cells - Li, Fengjie; Zhang, Rong; Hu, Changpeng; Ran, Qian; Xiang, Yang; Xiang, Lixin; Chen, Li; Yang, Yang; Li, Shengwen Calvin; Zhang, Gang; Li, Zhongjun (Frontiers in Cell and Developmental Biology, 2021)
Purpose Repairing the irradiation-induced osteogenic differentiation injury of bone marrow mesenchymal stem cells (BM-MSCs) is beneficial to recovering haematopoiesis injury in radiotherapy; however, its mechanism is elusive. Our study aimed to help meet the needs of understanding the effects of radiotherapy on BM-MSC osteogenic potential. Methods and Materials Balb/c mice and the BM-MSCs were used to evaluate the irradiation-induced osteogenic differentiation injury in vivo. The cellular and molecular characterization were applied to determine the mechanism for recovery of irradiation-derived haematopoiesis injuries. Results We report a functional role of IL-12 in acute irradiation hematopoietic injury recovery and intend to dissect the possible mechanisms through BM-MSC, other than the direct effect of IL-12 on hematopoietic stem and progenitor cells (HSPCs). Specifically, we show that early use of IL-12 enhanced the osteogenic differentiation of BM-MSCs through IL-12Rβ1/TYK2/STAT3 signaling; furthermore, IL-12 induced osteogenesis facilitated bone formation and irradiation hematopoiesis recovery when transplanted BM-MSCs in the femur of Balb/c mice. For the mechanism of action, we found that IL-12 receptor beta 1 (IL-12Rβ1) expression of irradiated BM-MSCs was upregulated rapidly, coincidentally consistent with early use of IL-12 induced osteogenic differentiation enhancement. IL-12Rβ1 and tyrosine kinase 2 gene (Tyk2) silencing experiments and phosphotyrosine of signal transducer and activator of transcription 3 (p-STAT3) suppression experiments indicated the IL-12Rβ1/TYK2/STAT3 signaling was essential in IL-12-induced osteogenic differentiation enhancement of BM-MSCs. Conclusion These findings suggested that IL-12 may exert BM-MSCs-based hematopoietic recovery by repairing osteogenic differentiation abilities damages through IL-12Rβ1/TYK2/STAT3 signaling pathway post-irradiation.